Estimated Health Risk of Cadmium and Chromium in Elderly Blood Cockle Consumers, Lantebung - Abd Gafur; Nasruddin Syam (Gema Lingkungan Kesehatan, 2026)
This study assessed the non-carcinogenic health risks of Cadmium (Cd) and Chromium (Cr) exposure through blood cockle (Anadara granosa) consumption among elderly residents in Lantebung, Makassar Strait. Blood cockle samples were collected from six purposively selected points, and Cd and Cr concentrations were analyzed. Health risks were estimated using intake calculations and the Risk Quotient (RQ). Cd and Cr concentrations were generally below national and international food safety limits. However, some elderly individuals, particularly frequent consumers, exceeded the non-carcinogenic risk threshold (RQ > 1). The highest risks were associated with specific sampling points, reflecting localized contamination. Risk factors included high consumption rates, long exposure duration, and lower body weight. These findings suggest that compliance with contaminant limits alone may not ensure safety for vulnerable populations. Regular environmental monitoring, risk communication for high-risk groups, and strengthened pollution control measures are recommended. Public health interventions, including periodic health screening and guidance on safe seafood consumption, are needed to reduce long-term health impacts.